Cartographic Journal (The World of Mapping) - Cartographic Journal (The World of Mapping) (Taylor & Francis, 2026)
The Cartographic Journal (first published in 1964) is an established peer reviewed journal of record and comment containing authoritative articles and international papers on all aspects of cartography, the science and technology of presenting, communicating and analysing spatial relationships by means of maps and other geographical representations of the Earth's surface. This includes coverage of related technologies where appropriate, for example, remote sensing, geographical information systems (GIS), the internet and global positioning systems. The Journal also publishes articles on social, political and historical aspects of cartography.
FI 0.4
Q3
Keywords: Biological; Earth & Environmental Food Science; Cartografía; Acuerdos transformativos; Transformative agreements; Teledetección; Sistemas de información geográfica